Acute and Subacute Toxic Aqueous Extract of the Leaves of Petroselinum Crispum Mill. in Male and Female Wistar Rats - Jacques, Kablan Kassi Jean; Nadia, Blahi Adelaïde; Roger, Kouakou Koffi; Seraphin, Diby Yao; Martin, Siapo Yao; Annick, Tahiri (European Scientific Journal, ESJ, 2021)
The present study is part of a vast program of the valorization of the medicinal flora and to help the populations to make a real profit from the use of plants in order to avoid any problem of poisoning. Petroselinum crispum Mill. (Apiaceae) is a plant, whose therapeutic virtues are diverse. The toxicological aspect of the aqueous extract of Petroselinum crispum leaves in male and female rats was investigated. The acute toxicity study with the single dose of 5000 mg/Kg body weight shows that the aqueous extract from the leaves of Petroselinum crispum is not toxic orally. According to Organisation for Economic Cooperation and Development (OECD) Guideline 423, the oral LD50 for this extract is greater than 5000 mg/kg body weight. In addition, the sub-acute toxicity study (OECD 407) showed that the aqueous extract from the leaves of Petroselinum crispum did not show any toxic effects at doses 50,100 and 200 mg/kg body weight and would have an orexigenic effect after 28 days of treatment. The different histological sections showed that the aqueous extract of Petroselinum crispum is not toxic on the vital organs and appears to be hepatoprotective.